Coupled Dynamic Response of an Offshore Multi-Purpose Floating Structure Suitable for Wind and Wave Energy Exploitation - Konispoliatis, Dimitrios N.; Manolas, Dimitrios I.; Voutsinas, Spyros G.; Mavrakos, Spyros A. (Frontiers in Energy Research, 2022)
This paper presents the coupled analysis performed in the frequency and time domain, considering a multi-purpose floating structure suitable for offshore wind and wave energy source exploitation. The floating structure encompasses an array of hydrodynamically interacting Oscillating Water Column (OWC) devices, moored through tensioned tethers as a Tension Leg Platform (TLP), and supports a 10 MW Wind Turbine (WT). The analysis is built to incorporate properly the solutions of the diffraction and the pressure- and motion-dependent radiation problems around the floating structure, the mooring lines characteristics, the OWCs characteristics, and the aerodynamics of the WT by accounting for the aerodynamic modelling of the rotor, the elastic modelling of the turbine components, namely the blades, the drive train, and the tower. Numerical results are obtained through the developed analysis methods, presenting the fundamental hydrodynamic properties of the platform, as well as the ultimate and fatigue loads at several locations on the structure expected to be imposed on it over its lifetime. The effect of the installation sites (i.e., environmental excitation) on the lifetime loads is investigated by comparing the estimated loads at various Mediterranean Sea and North Sea locations. Finally, the OWC effect, due to the air pressure oscillation inside the wave energy converters, is discussed, highlighting its significant influence on the hybrid system’s loading conditions.